Study and thinking skills - Custodio, Emelita S.; Achas, Amelita P.;Barlan, Jayson M.;Nolasco, Maria Fatima C. (Malabon City, Philippines : Mutya Publishing House, 2012)
This book is an instruction package for first year college students of the English language. In addition to the broad goal of developing the communicative competence of students in English, the worktext aims to consolidate the skills and knowledge needed by students to perform well in their studies in particular and in their lives in general.
Chapter 1. Study and learning styles -- Chapter 2. The library -- Chapter 3. The word -- Chapter 4. Reading skills development -- Chapter 5. Enhancing reading comprehension skills -- Chapter 6. The art of note taking -- Chapter 7. Reading and interpreting non-prose forms -- Chapter 8. The paragraph -- Chapter 9. Paragraph development -- Chapter 10. Discourse -- Chapter 11. Paragraph writing.
Includes bibliographical references.
Keywords: COMMUNICATION -- ENGLISH LANGUAGE